The Importance of Reflexivity in Program Development: A Case Study Involving Teaching Self-Defense to Middle School Girls in PE Class - Follo, Giovanna (Violence against women, 2024)
This research used a self-defense program to explore how middle school girls could change their perspectives on the gendered roles of victim and protector within an empowered self-defense approach. Taking the dual role of researcher and self-defense instructor, I developed a program to influence changing information strips directed toward gender norms, behavior, and discourse. Reflexive thematic analysis was utilized due to its intersection of the researcher's experience, literature, and theory. The research consisted of 40 girls journaling and 23 girls completing a post-program survey. Findings suggested that reflexive body techniques through self-defense could potentially impact internalized gendered information strips.